Linfomas en Altura - Morales Alfaro, Américo (2001)
They are registered 520 oncology patients in the National Hospital of South East EsSALUD (HNSE) of Cusco-Perú at 3340 m. above sea level in the period of 1996 to 1999, occupying the 4th place the hematologic neoplasia, after the mamma cancer, cervix cancer and prostatic cancer. They were reviewed 44 clinic histories of patients with malignant proliferative disease of leukocyte, 14 of which are death, we have 8 patients with acute leukaemia, 2 with multiple mieloma, a patient with histiocitosis and 33 patients with malignant lymphoma, of which 30 them fulfilled with criteria of inclusion expressed in this research. The results were the following: 1. The limphoproliferative syndrome occupy the 4th place in the HNSE, the prevalence of these neoplasia is of 9.24 for 100,000 inhabitants.  2. Female are the most affected (60%) 3. It presents with most frequency in elder of 60 years old (86.63%), the media age is of 50.3 years old, the elder of 60 years old are affected in a 30%. 4. The most frequent localization is the abdominal in a 53.84% in a 53.84%, it follows in frequency the axillary localization (19.23%), mediastinal space (11.53%). 5. About the distribution of the lymphomas along the gastrointestinal tract we appreciate that the 33% are located in the stomach and the 60% in the small intestine. 6. The most frequent clinic manifestations are the loose weight (63.3%), adenopathy and pain (40%), abdominal tumor and anorexia (33.3 %), fever (26.7%) paleness (16.6%) and ceplialalgia (13.3%). 7. The haemoglobin in the linphoproliferative syndrome in high altitude has a media of 13.759 with a standard deviation of 3. 181 and an standard error of 0.591; we have an evidence that the patients with diagnostic of leukaemia in high altitude, in a 75%, have value of haemoglobin minor of 10 gr/dl (p = 0.0008). 8. The 70.58% of patients with diagnostic of syndrome of limphoproliferative presents a high value of globular sedimentation rate (VSG), it means higher of 15 mm/h, being the media of 28.381 mm/h, with a standard desviation of 4.850. 9. The stadium II is the most frequent (38.46%), it follows in frequency the stadium IV (30.76%) and III (23.07%); it corresponds to advances stadiums 53.85%. 10. The patients with mediastinal tumoral localization are all with diagnostic in the stadiums III and IV. 11. The disease of Hodgkin represents the 6.7% of the limphoproliferative syndromes in the present study. 12. In high altitude the lymphomas non Hodgkin are predominant diffuse and the most frequent sub group comparatively are the diffuse mixed lymphomas. 13. The lymphomas non Hodgkin with tumoral localization in to abdominal level present a short term disease free, minor of 6 months (p=0,037). 14. In the patients that presented a long term disease free, the 63.63% present values of VSG between 16-30 mm/h; in the patients with short term disease free, the 66.66% present values of VSG higher of 30 mm/h. The 80% of the patients with VSG higher of 30 mm/h have been presented a short term disease free. 15. The values of lactic dehydrogenasa (DHL) higher of 400 U/l to the moment of the diagnostic present statistic relation with short term disease free (p=0.041) 16. The 100% of the patients that present a short term disease free have a poor answer to the treatment, the 92.85% of the patients that present a long term disease free are potentially healable.